1989
DOI: 10.1017/s0950268800030727
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A antibody in blood donors in North East Thames region: implications to prevention policies

Abstract: SUMMARYA total of 1786 blood donors were screened for the presence of anti-hepatitis A antibody (anti HAV). 64-5% of the donors were found to be positive. The prevalence of the antibody was found to be age-related, 55 % at 18 years and 75 % at 65 years. No relationship was noted between the presence of antibody, foreign travel or a specific destination. Assay of antibody levels in selected seropositive individuals gave a mean level of 5 0 IU/ml.The prevalence of infection in this selected population is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The overall rate of HAV positivity in the donor population measured in our study was 21%. In a similar study in 1989, based on blood donors in the North East Thames Region, Scott et al (1989) used an assay from another manufacturer to measure anti-HAV. They found a much higher rate (60%) of anti-HAV positivity.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of HAV positivity in the donor population measured in our study was 21%. In a similar study in 1989, based on blood donors in the North East Thames Region, Scott et al (1989) used an assay from another manufacturer to measure anti-HAV. They found a much higher rate (60%) of anti-HAV positivity.…”
Section: Discussionmentioning
confidence: 99%
“…The declining incidence of hepatitis A antibodies in the general population in the United Kingdom and elsewhere may lead to reduction in the efficacy of passive immunisation with normal human immunoglobulin and emphasised the need for active immunisation with an effective vaccine. During the evaluation by clinical trial of the currently licensed hepatitis A vaccine, screening for IgG hepatitis A antibodies by enzyme-linked immunoadsorbent assay showed the prevalence of antibodies to be 8% among first-year medical students aged 19-31 [Zuckerman et al, 19911. Other studies have demonstrated a relationship between both seroprevalence and age [Scott et al, 1989;Higgins et al, 19901 and continuing improvements in socioeconomic conditions and personal hygiene. As a consequence, the average age of exposure to hepatitis A virus (HAV) will increase with a paradoxical increase in clinical hepatitis and its severity.…”
Section: Introductionmentioning
confidence: 92%